Fibromyalgia: antecedent life events, disability, and causal attribution - Gonzalez, B.; Baptista, T. M.; Branco, J. C.; Ferreira, A. S. (Psychology, Health and Medicine, 2013)
This study aimed to evaluate the relation of disability and physical and mental health status with potentially traumatic life events (PTLE) before the onset of fibromyalgia in women diagnosed with this syndrome. We also investigated causal attribution of fibromyalgia to a triggering event, physical or psychological in nature, and its relation with the health measures and the adverse life events. The impact of fibromyalgia, physical and mental health status, pain, PTLE in childhood and not in childhood, and causal attribution were assessed in a sample of 50 women with fibromyalgia, aged 25-70 (M=46.96; SD=10.96). There were no statistically significant relations between the health measures (disability, physical and mental health, and pain) and the PTLE. The predominant attribution was to a physical event. There were no significant differences neither in the health measures across causal attribution status (Pillai's Trace=0.193; F(8,90)=1.200; p=.308; (2) (par)=.096) nor in the PTLE not in childhood (F(2,47)=1.063; p=.354; (2) (par)=.043). There were significant differences across causal attribution status in the PTLE in childhood (F(2,47)=3.590; p=.035; (2) (par)=.133), specifically between the group that made a psychological attribution and the group that made no attribution (C.I. 95%) 0.1805; 14.0468; (p=.043), with the former having a higher score of PTLE in childhood. The results raise questions about the importance of psychological aspects in the appraisal of the adverse events and its possible relation to the psychological functioning in women with fibromyalgia.